Status of milk quality at farmers field - SINGH, VIKRAM; GUPTA, JANCY (The Indian Journal of Animal Sciences, 2014)
The study was conducted on the clean milk production (CMP), to analyze the milk quality from producer to processing plant in cooperative system. To fulfill the objectives, a plan of work was prepared; under which 4 milk unions of Rajasthan Cooperative Dairy Federation (RCDF) were selected, viz. Alwar, Bhilwara, Bikaner and Hanumangarh. To analyze the milk quality, samples were collected from 3 levels of milk collection, viz. pail (farmer), Dairy Cooperative Society (DCS) and dock (district level) in cooperative system and tested at respective unions’ laboratory. The study revealed that as per ISO standards milk unions stands at ‘Very Good’ at pail, ‘Good’ at DCS and ‘Fair’ at dock level, respectively. Lack of incentives on CMP was perceived as very serious constraint by all the farmers.